Konservasi Pantai dan Daur Ulang Limbah Plastik menjadi Kerajinan Tangan - Agus Subaidi; Lili Supardi; Rizky Ria Fatim Hardimy (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
A clean beach indicates a healthy surrounding environment. Beach cleanliness cannot be separated from the role of the community to always protect it. One way is by not throwing garbage or waste carelessly. If the beach is dirty, it should be cleaned immediately so as not to cause bad effects. On the coast of Tlesah you can find plastic waste that is difficult to decompose and other waste that pollutes the environment. This requires an action. In this service, an activity was carried out, namely beach conservation and recycling of plastic waste into handicrafts. It aims to make the beach clean so that marine biota becomes healthy, provide knowledge on how to make handicrafts, create business opportunities from the handicrafts that have been made and instill awareness about cleanliness in the surrounding community. The methods used in this activity are observation, outreach and documentation. Socialization is carried out by directly involving the community in activities. The results obtained are that people are more aware of the importance of cleanliness and the benefits of recycling waste into valuable goods.